Licensing of Raw Agricultural Commodity Fumigation Applicators in Florida - Frederick M. Fishel (EDIS)
PI-151, a 3-page fact sheet by Frederick M. Fishel, explains the licensing and regulation of persons who apply restricted use fumigant pesticides to raw agricultural commodities in Florida. Published by the UF Pesticide Information Office, February 2007.